Chapter 10 The Family Constitution as an Instrument of Corporate Governance in Family-Owned Companies - Patrick Ulrich; Sarah Speidel (Emerald Publishing Limited, 2023)
In recent years, the corporate governance structures of family businesses have become increasingly important to the public. This is due not only to the increasing number of corporate successions but also to the (still) lower degree of formalization of corporate governance in family-owned companies. In this chapter, the authors analyze theoretical and empirical findings on family governance with a focus on family constitution and present the results of their own exploratory empirical survey conducted in 2017.
10.1108/978-1-83797-200-520231010; 10.1108/978-1-83797-200-520231010; Family Firms and Family Constitution; EBP099697173